RESPONSE OF IN-SITU PADDY STRAW MANAGEMENT PRACTICES ON MICROBIAL ACITVITY, ENZYMATIC ACTIVITY AND CROP PRODUCTIVITY IN SUBSEQUENT ZERO TILL MAIZE - S. TRIVENI and M. YAKADRI, G. RAJITHA, B. PADMAJA, M. MALLA REDDY, A. MADHAVI, S. NARENDER REDDY (The Journal of Research, PJTSAU, 2023)
Rice (Oryza sativa) - Maize (Zea mays L.) is one of the predominant cropping system of Telangana. The concept of zero tillage is gaining momentum in traditional areas under rice-maize sequence. The intensification of rice based cropping systems isresulting in a larger volume of rice straw being produced that, in turn, must be managed over shorter turnaround times betweencrops. The present study was conducted at College farm, College of Agriculture, Rajendranagar, Professor Jayashankar TelanganaState Agricultural University during rabi 2020-21 and 2021-22 with eight residue management practices (M1: Burning residuebefore sowing, M2: Retention of residue, M3: Removal of residue before sowing, M4: Incorporation at 15 DAS, M5: Incorporation at 15 DAS + SSP at equivalent to ‘P’ dose, M6: Spraying consortia of decomposers @ 10% of residue weight + surface retention, M7: Spraying consortia of decomposers @ 10% of residue weight + incorporation at 15 DAS, M8: Spraying consortia of decomposers @ 10% of residue weight + incorporation at 15 DAS + SSP at equivalent to ‘P’ dose and three fertility levels (S1: 75 % RDF, S2: 100% RDF and S3: 125 % RDF) laid out in strip plot design with three replications in both the years. The results of the study revealed that higher grain yield (6601 and 6999) and straw yield (8151 and 8555) were obtained with incorporation + consortium + SSP treatment in combination with 75 % RDF during rabi 2020-21 and 2021-22, respectively. Similarly bacterial and fungi population with higher dehydrogenase activity were recorded under incorporation + consortium + SSP treatment along with 125 % RDF in rabi 2020-21 and 2021-22. Hence, it can be concluded that incorporation of crop residues with SSP application equivalentto ‘P’ dose and microbial consortium along with the addition of 75 % RDF performed better than mere incorporation, removal, retention, retention + consortia and burning of residues in combination with 125 % RDF.